Cataract induction in an arthropod reveals how lens crystallins contribute to the formation of biological glass - Amartya T. Mitra; Shubham Rathore; Augusta Jester; Ruby Hyland-Brown; J. Hassert; Joshua B. Benoit; Annette Stowasser; Elke K. Buschbeck (PLoS ONE, 2025)
Lenses are vital components of well-functioning eyes and are crafted through the precise arrangement of proteins to achieve transparency and refractive ability. In addition to optical clarity for minimal scatter and absorption, proper placement of the lens within the eye is equally important for the formation of sharp, focused images on the retina. Maintaining these states is challenging due to dynamic and substantial post-embryonic eye and lens growth. Here, we gain insights into required processes through exploring the optical and visual consequences of silencing a key lens constituent in Thermonectus marmoratus sunburst diving beetle larvae. Using RNAi, we knocked down Lens3, a widely expressed cuticular lens protein during a period of substantial growth of their camera-type principal eyes. We show that lens3 RNAi results in the formation of opacities reminiscent of vertebrate lens ‘cataracts’, causing the projection of blurry and degraded images. Consequences of this are exacerbated in low-light conditions, evidenced by impaired hunting behaviour in this visually guided predator. Notably, lens focal lengths remained unchanged, suggesting that power and overall structure are preserved despite the absence of this major component. Further, we did not detect significant shifts in the in-vivo refractive states of cataract-afflicted larvae. This in stark contrast with findings in vertebrates, in which form-deprivation or the attenuation of image contrast, results in the dysregulation of eye growth, causing refractive errors such as myopia. Our results provide insights into arthropod lens construction and align with previous findings which point towards visual input being inconsequential for maintaining correctly focused eyes in this group. Our findings highlight the utility of T. marmoratus as a tractable model system to probe the aetiology of lens cataracts and refractive errors.